Estimates and trends in death and disability from atrial fibrillation/atrial flutter due to high sodium intake, China, 1990 to 2019 - Qingwen Yu; Lijun Zhao; Ting Tang; Ziyi Xin; Lanlan Feng; Xiyun Rao; Yongmin Shi; Xuhan Tong; Siqi Hu; Yao You; Shenghui Zhang; Jiake Tang; et al. (BMC Cardiovascular Disorders)
Abstract Objective The effect of sodium intake on atrial fibrillation (AF)/atrial flutter (AFL), with respect to sex and age, has yet to be elucidated. This study aims to compare long-term trends in AF/AFL death and disability due to high sodium intake in China from 1990 to 2019. Methods We utilized data from the Global Burden of Disease study to assess the mortality and disability burden of AF/AFL attributable to high sodium intake (> 5 g/d) in China from 1990 to 2019. Overtime trends and average annual percentage change (AAPC) were analyzed with adjustments for age, sex, period, and cohorts. Results In 2019, the number of AF/AFL deaths and disability-adjusted life years attributable to high sodium intake were 4209.944 (95% UI: [1250.690-8718.238]) and 235484.586 (95% UI: [89136.783-428566.694]), with males comprising 44.81% and 51.95% of cases, respectively. The age-standardized mortality rates (ASMRs) and age-standardized disability rates (ASDRs) of AF/AFL attributable to high sodium intake exhibited downward trends from 1990 to 2019 in China. The AAPC was − 0.221(95% CI: -0.321–0.121)and − 0.631(95% CI: -0.816–0.446) for AF/AFL, respectively. An upward trend was observed in ASMRs for AF and AFL, attributable to high sodium intake due to high salt intake at ages 30–34, 35–39, and 40–44. With an increase in age, the AAPC for ASMRs increased correspondingly, and the AAPC for ASDRs exhibited a decreasing trend. Conclusions Our findings provide strong evidence that high sodium levels in China significantly affect standard ASMRs and ASDRs for AF and AFL. Notably, different patterns of change are identified across various age groups, emphasizing the pronounced effect of salt reduction on AF and AFL.